Technology Business Incubation: An overview of the state of knowledge. (April 2016) - Mian, Sarfraz; Lamine, Wadid; Fayolle, Alain
Abstract: This paper introduces Technology Business Incubation (TBI) as a field of study and practice, exploring the concept, its evolution, and scholarship. Science parks, incubators and accelerators are TBI mechanisms considered to be important policy tools for supporting innovation and technology-oriented entrepreneurial growth. Their popularity is premised on the belief that these mechanisms provide critical value-added inputs essential for the creation and development of innovative Technology-Based Firms (TBFs). However, determining what type of TBI mechanisms and policies are most conducive to achieving the desired results is very much mission-driven and context-specific. A review of the past three decades of incubation literature, emerging practice, and future trends reveals that despite ongoing debate about their contribution and challenges, the future of TBIs is promising, and there are rich opportunities for research.